Laws for health and care worker protection and rights: A study of 182 countries. - Matthew M Kavanagh; Adi Radakrishnan; Vishakh Unnikrishnan; Giorgio Cometto; Catherine Kane; Eric A Friedman; Varsha Srivatsan; Luis Gil Abinader; James Campbell; Health & Care Worker Policy Lab (PLOS Global Public Health)
The unprecedented and multi-faceted challenges health and care workers faced during the COVID-19 pandemic inspired the world's health ministers to call for a new Global Health and Care Worker Compact at the 74th World Health Assembly in 2021. The Care Compact identifies key areas where governments can use law and policy to prevent harm, provide support, ensure inclusivity, and safeguard rights of health and care workers toward improving population health. Using policy surveillance methods, we conducted an empirical analysis of the national law and policy environments on health and care workers' protection and rights in 182 countries. Across 10 indicators, 1,262 laws and policies were identified and analyzed for their alignment with the international legal standards. Analysis shows significant gaps. 62% of all national laws are aligned. Nearly every country has multiple areas where national laws are not yet aligned with the Care Compact. Though alignment is feasible. In 5 of 6 regions at least one country has laws aligned on all indicators. Geographic region was not a significant predictor of alignment, while income level was only weakly associated. Comparing the key legal issues facing health and care workers, well over half of countries studied are fully aligned with the Care Compact on occupational health and safety, fair remuneration, enabling work environments, freedom of association, and collective bargaining. Approximately 50% of countries studied are fully aligned on protections against violence and harassment in the workplace and whistleblower protections. But less than 25% are fully aligned on access to health services in occupational settings and equal treatment and non-discrimination. Together this analysis highlights the need for, and opportunity of, law reform in countries throughout the world to elevate and protect the rights and well-being of health and care workers and, in doing so, improve health systems.